Сказочные повести - Прокофьева Софья Леонидовна (Школьная библиотека, 2012)
Экземпляры: М/а ДБ (20130507) / Инвентарный номер: 99604 / Цена: 118.80 / Авт.знак: П 80 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6